Tactics: the art and science of success - "De Bono, Edward" (London, 2011)
This book is based upon 50 interviews with men and women - eg Chris Bonington, Mark McCormack, Terence Conran and Malcolm Forbes - who have been outstandingly successful in a variety of fields. With his usual perceptiveness, Edward de Bono analyses their different paths to success, revealing that underneath their different styles and their greatly different personal qualities are a few characteristics which are common to all successful people. De Bono provides the lessons for anyone seeking success in their lives.
Keywords: Personal success